PROCESS THE IMPACT OF METHODICAL PRINCIPLES ON THE ARRANGEMENT OF THE EDUCATIONAL PLANNING (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Methodical principles are special and important in the teaching process. This article discusses the role of methodological principles in teaching foreign languages. Examples of scientists’ opinions about methodological principles are given.